2012
DOI: 10.1186/1479-5876-10-122
|View full text |Cite
|
Sign up to set email alerts
|

Transient and intensive pharmacological immunosuppression fails to improve AAV-based liver gene transfer in non-human primates

Abstract: BackgroundAdeno-associated vectors (rAAV) have been used to attain long-term liver gene expression. In humans, the cellular immune response poses a serious obstacle for transgene persistence while neutralizing humoral immunity curtails re-administration. Porphobilinogen deaminase (PBGD) haploinsufficiency (acute intermittent porphyria) benefits from liver gene transfer in mouse models and clinical trials are about to begin. In this work, we sought to study in non-human primates the feasibility of repeated gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 26 publications
(42 reference statements)
1
48
0
Order By: Relevance
“…92,99,123 Most probably, the PBGD transgene protein will not elicit immune responses in a clinical trial for AIP.…”
Section: Immune Response To the Transgene Proteinmentioning
confidence: 98%
See 4 more Smart Citations
“…92,99,123 Most probably, the PBGD transgene protein will not elicit immune responses in a clinical trial for AIP.…”
Section: Immune Response To the Transgene Proteinmentioning
confidence: 98%
“…Additionally, human capsid-specific T cells were found to produce interferon-γ, a cytokine that upregulates the major histocompatibility complex I (MHC I) molecules that are critical for CD8 + target cell recognition, whereas those from NHP T cells were less efficient in this regard. 108 Coadministration of an immunosuppression protocol that included mycophenolate mofetil (MMF) with rAAV vector does not induce toxicity in NHP and does not meaningfully improve rAAV5-mediated gene expression 123 (Figure 4). However, Montenegro-Miranda et al 124 demonstrated that in Gunn rats MMF inhibited the synthesis of the complementary DNA strand following entry of the rAAV into the target cells.…”
Section: B Adaptive Immune Response To Raav Vectorsmentioning
confidence: 99%
See 3 more Smart Citations